2018
DOI: 10.1016/j.neuron.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

NIH/Kennedy Center Workshop on Music and the Brain: Finding Harmony

Abstract: The National Institutes of Health and John F. Kennedy Center for the Performing Arts convened a panel of experts to discuss the current state of research on music and the brain. The panel generated research recommendations to accelerate the study of music's effects on the brain and the implications for human health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 10 publications
0
38
0
Order By: Relevance
“…More recently, neuroimaging studies have shown that participating in musical activities engages a multimodal network of brain regions involved in hearing, movement, emotion, pleasure and memory (47)(48)(49), thus allowing transfer of music-related therapeutic effects to non-musical domains (50-54) through structural and functional brain changes (55)(56)(57)(58). However, a direct link between effects of music interventions and changes in the brain is yet to be demonstrated in autism (59,60), and was our aim here.…”
Section: Introductionmentioning
confidence: 98%
“…More recently, neuroimaging studies have shown that participating in musical activities engages a multimodal network of brain regions involved in hearing, movement, emotion, pleasure and memory (47)(48)(49), thus allowing transfer of music-related therapeutic effects to non-musical domains (50-54) through structural and functional brain changes (55)(56)(57)(58). However, a direct link between effects of music interventions and changes in the brain is yet to be demonstrated in autism (59,60), and was our aim here.…”
Section: Introductionmentioning
confidence: 98%
“…More recently, neuroimaging studies have shown that participating in musical activities engages a multimodal network of brain regions involved in hearing, movement, emotion, pleasure and memory 27 31 , thus allowing transfer of music-related therapeutic effects to non-musical domains 32 through structural and functional brain changes 33 , 34 . However, a direct link between effects of music interventions and changes in the brain is yet to be demonstrated in autism 35 , 36 and was our aim here.…”
Section: Introductionmentioning
confidence: 99%
“…The growing interest in music interventions for children with ASD has been in part inspired by research hinting that music might be a potential vehicle for emotional understanding [24,25] and emotion regulation [26,27] in ASD. There is growing evidence that music interventions can improve ASD symptoms and comorbidities in children with ASD [28] as well as social interactions, communication, and emotional engagement [29,30,31]. Given these findings, it is unsurprising that the interest in music as a therapy for ASD has gained traction in recent years, and that children with ASD have been identified as a potential clinical group that might benefit from music-based interventions [31].…”
Section: Introductionmentioning
confidence: 99%